Boric Acid Mediated Formation and Doping of NiOx Layers for Perovskite Solar Cells with Efficiency over 21%. Issue 4 (4th March 2021) - Ge, Bing; Lin, Ze Qing; Zhou, Zi Ren; Qiao, Hong Wei; Chen, Ai Ping; Hou, Yu; Yang, Shuang; Yang, Hua Gui
Abstract : Metal halide perovskite solar cells (PSCs) have emerged as one of the most promising photovoltaic technologies. For inverted planar PSCs, nickel oxide (NiO x ) layers, as inorganic p‐type semiconductors, are competitive hole transport layers (HTLs) because of their low cost, chemical stability, and easy preparation. However, their inferior device performance still lags behind the devices using organic HTLs. Herein, a boric acid‐assisted strategy for NiO x HTLs is reported that enables compact film deposition and electronic modulation. Boron doping can enhance conductivity and deepen the valence band edge, leading to efficient hole extraction and transport. A methylammonium lead iodide (MAPbI3 ) photovoltaic device based on our strategy achieves an optimized efficiency of 21.40% with a high open voltage of 1.131 V and a high fill factor of 80.9% with negligible hysteresis, as well as excellent stability. Abstract : A simple boric acid assisted strategy is used to tailor the morphology and optoelectronic properties of NiO x with a solar cell efficiency over 21%, a high open‐voltage of 1.131 V, and a high fill factor of 80.9%. Enhanced hole extraction and transport are responsible for the high performance inverted planar methylammonium lead iodide photovoltaic devices.